A problemática da inadimplência na garantia do direito fundamental à subsistência do alimentado - Simões, Chames Rayol Maluf Braid (2022)
The Covid-19 Pandemic surprised by fast contagion amongst people and the way national and international institutions dealt with the problem. The economic crisis that followed alongside this pandemic period made it difficult to fulfill obligations of the most varied orders. One of the main consequences, in the context of private life, was the high default of maintenance obligations of a judicial nature. This text aims to analyze that there is an ethical duty to pay attention and support to the most vulnerable people within these private relationships. Given this circumstance, the problem that guides this research is: how is the socioeconomic organization of judicial decisions within the scope of the Court of Justice of the State of Maranhão due to the economic restructuring caused by the Covid-19 pandemic? As a central hypothesis, it starts from the idea that if the new structures caused by the Covid-19 Pandemic are understood within an economic crisis perspective, then the processes of imposition and review of alimony payment must be adequate to reduce the financial capacity of food debtors. In order to reach this central and main objective, some specific paths must be taken, in order to make the understanding more methodologically viable. First, it will be necessary to conceptualize food as a fundamental social right, based on the principle of human dignity, and then, to categorize the elements and assumptions of the obligation to provide food. Methodologically, then, the form adopted intends to categorize the elements of civil and constitutional law as a basic structuring for the application in the analysis of the treatment given by the Court of Justice of Maranhão to cases related to the obligation to provide food. Finally, to give pragmatic and effective airs to the text, collegiate decisions of the Court of Justice of Maranhão (TJMA) are analyzed regarding the context of the Covid-19 Pandemic and the resources that deal with the review of alimony during this period.